2003
DOI: 10.1080/10611860305553
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl Derivatives of Dopamine and l -dopa as Anti-Parkinson Prodrugs: Synthesis, Pharmacological Activity and In Vitro Stability Studies

Abstract: Novel glycosyl derivatives of dopamine and L-dopa (I-IV) are synthesized in order to overcome the problem of blood-brain barrier low permeability of dopamine and of low bioavailability of its precursor L-dopa. Esters synthesized link dopamine and L-dopa, by a succinyl linker, to C-3 position of glucose (I and II) and to C-6 of galactose (II and IV). The chemical and enzymatic stabilities of esters synthesized were evaluated in order to determine both their stability in aqueous medium and their feasibility in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 0 publications
0
44
2
Order By: Relevance
“…3 One strategy to improve poor drug uptake in the brain is to administer compounds as prodrugs that can be shuttled by transporters specifically expressed at the BBB. 4 Using this approach, researchers have succeeded in designing drug-carrier conjugates that can specifically interact with glucose transporters (GluT1), 5 amino acid transporters (LAT1), 6 and choline transporters, 7 thereby targeting the drugs to the brain. For cationic drugs, however, the transporters that may move them across BBB remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…3 One strategy to improve poor drug uptake in the brain is to administer compounds as prodrugs that can be shuttled by transporters specifically expressed at the BBB. 4 Using this approach, researchers have succeeded in designing drug-carrier conjugates that can specifically interact with glucose transporters (GluT1), 5 amino acid transporters (LAT1), 6 and choline transporters, 7 thereby targeting the drugs to the brain. For cationic drugs, however, the transporters that may move them across BBB remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the LD esters with C-3 position of glucose and C-6 position of galactose were synthesized (80 and 81 respectively) [50]. The obtained results indicate that compounds 80 and 81 appeared stable in buffered solution (pH 7.4) and in rat plasma.…”
Section: Glycosyl Prodrugs Of Ldmentioning
confidence: 92%
“…Furthermore, another shortcoming of dopamine is that although it cannot cross the BBB because of its polarity, it is nonetheless very active peripherally, thus causing a broad number of adverse cardiovascular effects. On the contrary, GALDA can reliably ward off peripheral side effects thanks to its stable plasma concentration determined by a gradual release of low amounts of dopamine directly in the CNS [12]. A recent study has demonstrated that galactosylation of N -nitro-L-arginine (NA), a non-selective nitric oxide synthase (NOS) inhibitor, generates the prodrug NAGAL Fig. (2).…”
Section: Brainmentioning
confidence: 98%
“…In particular, the hydroxyl group at the carbon 6'-position of the sugar is the most potential functional group to which the drug molecule attaches in order to maintain the affinity for the GLUT-1 transporter [8]. For instance, drugs as 7-chlorokynurenic acid [9], nipecotic acid [10] and dopamine [11][12] that have been conjugated with D-galactose have revealed enhanced activities in the CNS. Dopamine (DA) covalently linked to D-galactose (GALDA) by a succinic spacer Fig.…”
Section: Brainmentioning
confidence: 99%
See 1 more Smart Citation